Labor productivity standards in Texas school foodservice operations - Sherrin, A. Rachelle; Bednar, Carolyn; Kwon, Junehee (My University, 2010)
Purpose of this research was to investigate utilization of labor productivity standards and variables that affect productivity in Texas school foodservice operations. A questionnaire was developed, validated, and pilot tested, then mailed to 200 randomly selected Texas school foodservice directors. Descriptive statistics for variables were calculated. MANOVA and Pearson’s Product Moment correlation were used to test relationships between variables affecting labor productivity. The most common labor standard used was meals per labor hour (MPLH); both MPLH and labor cost as a percentage of revenue (%LABOR) were utilized more frequently in larger size districts. Meal equivalent (ME) conversions were most commonly defined as: 2 breakfasts = ME; $2.00 = ME; and 3 or 4 after-school snacks = ME. There was little consistency in use of labor productivity standards and ME conversions in Texas school foodservice operations, which limits their validity for external benchmarking. However, these standards can be used internally to effectively forecast labor needs, aid decisions about productivity, and hold employees accountable for their time.
Keywords: Labor productivity; Standards; Schools; Foodservice; Texas